Adapting playware to rehabilitation practices - Balslev Nielsen, C.; Hautop Lund, H. (International Journal of Computer Science in Sport, 2012)
We describe how playware and games may become adaptive to the interaction of the individual user and how therapists use this adaptation property to apply modular interactive tiles in rehabilitation practices that demand highly individualized training. Therapists may use the interactive modular tiles to provide treatment for a large number of patients who receive hospital, municipality or home care, although the tiles can as well be used for prevention with elderly or for fitness with normal people. In this paper, we describe the extensive use of the modular tiles with cardiac patients, smoker`s lung (COLD) patients and stroke patients in hospitals and in the private homes of patients and elderly. Through a qualitative research methodology of the new practice with the tiles, we find that therapists are using the modular aspect of the tiles for personalized training of a vast variety of elderly patients modulating exercises and difficulty levels. We also find that in physical games there are individual differences in patient interaction capabilities and styles, and that modularity allows the therapist to adapt exercises to the individual patient`s capabilities.